POSSIBLE TIMING OF THE TRANSITION FROM PRE-INDUSTRIAL TO INDUSTRIAL CLIMATE IN THE CENTRAL TO NORTHERN OF SWEDEN, BASED ON PROXY DATA FROM TREE-RINGS - Falkensjö Oppenheim, Mika (2022)
Earth’s climate has varied through time, with orbital forcing as the most dominant force on the climate system the last million years, causing glacial-interglacial cycles. The last glacial period ended about 11.6 thousand years (kyr), ago and the last interglacial maximum around 6.5 kyr ago. A cooling trend towards a new glacial period followed, interrupted by the present human caused global warming, mainly due to burning of fossil carbon. The United Nations Framework Convention on Climate Change (UNFCCC) agreed upon the goal of the Paris Agreement 2015, with the aim of holding the increase in the global average temperature to below 1.5 – 2 ºC from pre-industrial temperatures. The Intergovernmental Panel on Climate Change (IPCC) has defined the pre-industrial baseline to values of 1850-1900 CE, a period when global emissions of greenhouse gases already had raised since the industrial revolution ca 1750 CE, and possibly already have had effects on the temperature. The phenomenon of Arctic Amplification is a more pronounced warming in the Arctic region, with a present temperature rise of more than doubled compared to the global mean. Indications of an earlier transition from pre-industrial to industrial climate in high northern latitudes have been noticed and the aim in this thesis was to further explore this timing of the transition from pre-industrial to industrial climate in high northern latitudes. To do so, tree-rings have been used to reconstruct past temperatures. Tree-rings provides a variety of proxies used for climate reconstructions, with the benefit of being easily accessed, well replicated and available in regions suitable for climate studies. In the Fennoscandian region, correlation between climate and tree-rings has proven to be good, which has led to an extensive tradition of dendroclimatology. Here, updated tree-ring width (TRW) and maximum latewood density (MXD) chronologies from Ammarnäs are presented, built from Scots Pine wood sources, living and dead (preserved on the ground). The MXD ...